Partnerstwo publiczno-prywatne - zarys problemu - Hajdys, Dagmara (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article is about the co-operations between the public and the private sector in the frames of public and private partnership. The act about public and private partnership gives the chance to develop the co-operation between the public and the private sector and to realize a wider range of public services. The article discusses basic matters connected with carrying out the duties in the frames of public and private partnerships. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 133-142